English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

Greetings,

You're expression looks a lot like something you've dealt with before, if you don't let the radicals scare you, you're dealing with an equation of the form (a - b)(c + d).

So it's just a matter of doing distribution...

= (2 5^1/2-7)(2 5^1/2+4)
= (2 5^1/2*2 5^1/2 +2 5^1/2*4 -7 * 2 5^1/2 - 7*4)
= 4 * 5+8 5^1/2 -14 5^1/2 - 28
= 20 + 8 5^1/2 -14 5^1/2 - 28
..
so collect like terms
= -8 - 6 5^1/2
= -2(4+3 5 1/2)

That should be your answer...

Hope this helps.

Mark

2007-06-27 14:02:43 · answer #1 · answered by Mark B 2 · 0 0

What does the 2 5 mean? Is it 25? Is it 2*5^1/2? Is it 2+5^1/2? etc.

I'll assume its 25.
So answer is (5-7)(5+4) = -2*9 = -18

2007-06-27 13:51:08 · answer #2 · answered by ironduke8159 7 · 0 0

(2 5^1/2-7)(2 5^1/2+4)
25^1/2 means square root of 25 which is 5

so (5-7)(5+4)
-2 x 9
= -18

2007-06-27 21:37:11 · answer #3 · answered by sweet n simple 5 · 0 0

fedest.com, questions and answers